2019
DOI: 10.3389/fevo.2019.00414
|View full text |Cite
|
Sign up to set email alerts
|

Plant Stimuli and Their Impact on Brown Marmorated Stink Bug Dispersal and Host Selection

Abstract: A diverse diet in polyphagous insects satisfies changing nutritional needs but the choice of host plant may vary throughout the insect and plant life cycle. The behaviors associated with host choice in the immature stages may differ from the egg laying site chosen by the mother. To evaluate this for an important agricultural pest, we looked at host choice over two growing seasons for the invasive Halyomorpha halys. H. halys has a host breadth of over 170 known species in its invaded range and adults can satisf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 44 publications
1
18
0
Order By: Relevance
“…The hedgerow study did show that lures increased the number of BMSB seen by beating, especially to sticky panels where the lures were exposed (unsurprising). The study was useful to confirm the most efficient combination of lure and trap under local conditions, and the results unsurprisingly confirmed an improvement from the higher loading, reported by Acebes-Doria et al [49]. The results helped with the development of the first hedgerow transect study, which showed significantly greater sensitivity of beating trays over traps while avoiding the potential bias caused by the attraction of BMSB to the pheromone.…”
Section: Discussionsupporting
confidence: 73%
“…The hedgerow study did show that lures increased the number of BMSB seen by beating, especially to sticky panels where the lures were exposed (unsurprising). The study was useful to confirm the most efficient combination of lure and trap under local conditions, and the results unsurprisingly confirmed an improvement from the higher loading, reported by Acebes-Doria et al [49]. The results helped with the development of the first hedgerow transect study, which showed significantly greater sensitivity of beating trays over traps while avoiding the potential bias caused by the attraction of BMSB to the pheromone.…”
Section: Discussionsupporting
confidence: 73%
“…Population densities of BMSBs appear to be linked to the presence of host plants at specific phenological stages (Blaauw et al 2019;Soergel et al 2015). Large populations are found on seeding plants (Nielsen et al 2016), implying that they are particularly appealing to BMSBs.…”
Section: Discussionmentioning
confidence: 99%
“…Hatching almost simultaneously from an egg mass (Endo et al 2019), first instar nymphs feed first on the surface of their egg chorion and in the process obtain essential gut symbionts deposited by their mother during oviposition (Taylor et al 2014). The physical well-being of all five nymphal instars is dependent upon the host plant (or its surrounding) selected by their mother which -in turn -may partially depend upon the plant's phenological stage (Blaauw et al 2019;Funayama 2004). Nymphs are incapable of flight but otherwise closely resemble adults.…”
Section: The Brown Marmorated Stink Bugmentioning
confidence: 99%
See 2 more Smart Citations